Changes in photosynthesis, pigment composition and glutathione contents in two Antarctic lichens during a light stress and recovery - Balarinová, K.; Barták, Miloš, 1963-; Hazdrová, J.; Hájek, Josef, 1974-; Jílková, J. (Photosynthetica)
Over last decades, several studies have been focused on short-term high light stress in lichens under laboratory conditions. Such studies reported a strong photoinhibition of photosynthesis accompanied by a partial photodestruction of PSII, involvement of photoprotective mechanisms, and resynthetic processes into gradual recovery. In our paper, we applied medium [800 μmol(photon) m-2 s-1] light stress to induce negative changes in PSII funcioning as well as pigment and glutathione (GSH) content in two Antarctic fruticose lichen species. Chlorophyll (Chl) fluorescence parameters, such as potential and effective quantum yield of photosynthetic processes and fast transients (OJIP) recorded during high light exposition and recovery, revealed that Usnea antarctica was less susceptible to photoinhibition than U. aurantiaco-atra. This might be supported by a more pronounced high light-induced reduction in Chl a and b contents in U. aurantiaco-atra compared with U. antarctica. In both experimental species, total GSH showed an initial increase during the first 30-40 min of high light treatment followed by a decrease (60 min) and an increase during dark recovery. Full GSH recovery, however, was not finished in U. aurantiaco-atra even after 5 h indicating lower capacity of photoprotective mechanisms in the species. OJIP curves showed high light-induced decrease in both species, however, the recovery of the OJIPs shape to pre-photoinhibitory values was faster and more apparent in U. antarctica than in U. aurantiaco-atra. The results are discussed in terms of sensitivity of the two species to photoinhibition and their photosynthetic performance in natural environment. K. Balarinová, M. Barták, J. Hazdrová, J. Hájek, J. Jílková. Obsahuje bibliografii